Evaluating the Therapeutic Mechanisms of Selected Active Compounds in Houttuynia cordata Thunb. in Pulmonary Fibrosis via Network Pharmacology Analysis - Zhu, De-Wei; Yu, Qun; Sun, Ji-Jia; Shen, Yun-Hui (Frontiers in Pharmacology, 2021)
Pulmonary fibrosis, a common outcome of pulmonary interstitial disease of various different etiologies, is one of the most important causes of respiratory failure. Houttuynia cordata Thunb. (Family: Saururaceae) (H. cordata), as has been reported, is a Chinese herbal medicine commonly used to treat upper respiratory tract infection and bronchitis. Our previous study has proved that sodium houttuyfonate (an addition compound from sodium bisulfite and houttuynin) had beneficial effects in the prevention of pulmonary fibrosis (PF) induced by bleomycin (BLM) in mice. In the present study, network pharmacology was used to investigate the efficiency and potential mechanisms of H. cordata in PF treatment. Upon manually collected from literature and databases such as TCMSP and TCM-ID, 10 known representative ingredients of H. cordata species were screened. Then, the prediction of the potential active ingredients, action targets and signaling pathways were conducted through Gene Ontology (GO), protein-protein interaction (PPI) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses. The results of network pharmacology prediction suggested that H. cordata may act through multiple signaling pathways to alleviate PF, including the phosphatidylinositol 3-kinase-protein kinase B (PI3K/AKT) pathways, mitogen-activated protein kinase (MAPK) pathways, the tumor necrosis factor (TNF) pathways and interleukin-17 (IL-17) signaling pathway, et al. Molecular docking experiments showed that the chemical constituents of H. cordata had good affinity with TNF, MAPK1, and AKT1. And using lipopolysaccharide (LPS) induced A549 cells, a model was established to verify the anti-pulmonary fibrosis effects and related mechanisms of H. cordata relevant constituents. Finally, these evidences collectively suggest H. cordata may alleviate PF progression via the PI3K/Akt, MAPK and TNF signaling pathways and provide novel insights to verify the mechanism of H. cordata in the treatment of PF.